Confirming Carneiro: Resource Scarcity and Pre-Modern Warfare (Global Journal of Human-Social Science, 2023)
In 1970 Robert Carneiro introduced a theory called circumscription The theory suggests exposure to certain environmental conditions is the main determinant for conflict in the premodern era Well-received in some circles others scrutinized whether the theory was as capable as it claimed See for instance the symposium published by American Behavioral Scientist 31 4 March April Though disagreement remains as to whether Carneiro s theory retains any merit the results of empirical tests of his theory more often than not fall in his favor Carneiro 1988 See also Deflem 1999 This paper adds to those empirical results and confirms environmental conditions play a role in the presence or absence of war
Keywords: resource scarcity; conflict; war; circumscription theory; carneiro